The prevalence of HBV, HCV and HIV infections among Iranian infertile couples referring to Royan institute infertility clinic: A cross-sectional study - Mehrangiz Zangeneh; Maryam Sedaghat Jou; Mohammad Ali Sadighi Gilani; Mahin Jamshidi Makiani; Shaghayegh Sadeghinia; Reza Salman Yazdi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: The role of the screening protocol for viral hepatitis and human immuunodeficiency virus (HIV) infections among infertile couples were seldom investigated. Objective: The present study was performed to assess the prevalence of hepatitis B virus (HBV), hepatitis C virus (HCV) and HIV infections among infertile couples referring to infertility clinic of Royan Institute. Materials and Methods: This analytical cross-sectional study was performed on 21673 infertile couples referring to infertility clinic of Royan Institute between 2009 and 2014. Serological findings for viral hepatitis B, C and HIV infection were gathered herewith demographic data of the study participants through the study checklist. Ultimately, 302 couples who had at least one positive result in their serological tests were included in the statistical analysis. Results: The HBV and HCV infections prevalence among study participants were 0.57% and 0.148% respectively; only two cases had HIV infection. HBV and HCV infections prevalence had significant association with the gender of participants, but there was no significant relationship between these infections and infertility types. Conclusion: Viral hepatitis infections screening among infertile couples undergoing assisted reproductive techniques needs more attention.